A post-Kaleckian econometric analysis of interest rates, income distribution, capacity utilization, accumulation and profit rates: the case of Italy - Ozan Ekin Kurt (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
The aim of this paper is to analyze the effects of interest rates on rates of capacity utilization, capital accumulation and profit in Italy within a post-Kaleckian theoretical framework. The model employed in the analysis, which was developed by Hein/Schoder (2011), is based on monetary- authority-controlled real long-term interest rates that affect the functional distribution of income. Interest rates directly and indirectly affect the equilibrium rates of capacity utilization, accumulation and profit at a given debt-capital ratio. Our findings based on two econometric methods revealed that a higher real long-term interest rate has an adverse effect on these three endogenous variables in the Italian economy.
Keywords: E12; E21; E22; E25; E43; 330; Interest rates; Monetary policy; Functional income distribution; Capacity utilization; Capital accumulation; Profit rates; Post-Keynesian economics